2004
DOI: 10.1002/elps.200305843
|View full text |Cite
|
Sign up to set email alerts
|

High‐performance liquid chromatography and capillary electrophoresis: Methodological challenges for the determination of biologically relevant low‐aliphatic aldehydes in human saliva

Abstract: Tobacco smoke is involved in the pathogenesis of cardiovascular and respiratory diseases and also has a local toxic effect in the oral cavity. Low-aliphatic aldehydes, such as formaldehyde, acetaldehyde and acrolein, are among the main components of mainstream cigarette smoke and their local noxious and carcinogenic effects in the oral cavity and upper gastrointestinal tract are well-known. Although various studies have been performed so far to determine their content in cigarette smoke, none has included the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…Based on this preclinical evidence, we hypothesized that increased airway inflammation, manifested by high concentrations of myeloperoxidase (MPO), PGP, and LTB 4 , would be present in human smokers and those with COPD as a result of selective inhibition of the aminopeptidase activity of LTA 4 H. Furthermore, we hypothesize that alterations to the LTA 4 H-PGP pathway will correlate with clinical disease. Finally, we sought to determine whether once this pathway is initiated, there is ongoing selective LTA 4 H aminopeptidase inactivation through actions of acrolein, a component found in cigarette smoke (16,17) and in current smokers (18)(19)(20)(21) and former smokers with COPD (22), leading to a feed-forward process resulting in PGP accumulation and disease progression. Some of the results of these studies have been previously reported in the form of abstracts (23,24).…”
mentioning
confidence: 99%
“…Based on this preclinical evidence, we hypothesized that increased airway inflammation, manifested by high concentrations of myeloperoxidase (MPO), PGP, and LTB 4 , would be present in human smokers and those with COPD as a result of selective inhibition of the aminopeptidase activity of LTA 4 H. Furthermore, we hypothesize that alterations to the LTA 4 H-PGP pathway will correlate with clinical disease. Finally, we sought to determine whether once this pathway is initiated, there is ongoing selective LTA 4 H aminopeptidase inactivation through actions of acrolein, a component found in cigarette smoke (16,17) and in current smokers (18)(19)(20)(21) and former smokers with COPD (22), leading to a feed-forward process resulting in PGP accumulation and disease progression. Some of the results of these studies have been previously reported in the form of abstracts (23,24).…”
mentioning
confidence: 99%
“…Mainstream CS contains over 90 ppm acrolein (19), and indoor levels of acrolein can be as high as 1 mg/m 3 (0.2 ppm), especially in smoking areas (20,21). Estimates of acrolein within airway secretions or tracheal aspirates from smokers indicate its presence at 1-10 mM (22,23), concentrations that are sufficient to induce major functional effects on several cell types. Acrolein is itself recognized as one of the greatest noncancer health risks of all organic air pollutants, and has been associated with decreased respiratory function in the United States (24,25).…”
mentioning
confidence: 99%
“…2A LODs and LOQs. Despite the urine was diluted 20 times with water before its analysis, the method proposed provided smaller LODs for the aldehydes than those obtained by the CE methods described in the literature for the analysis of these carbonyl compounds in matrices other than air samples [11,14,16,17,19]. Furthermore, to our knowledge, the method proposed represents the first approach for the CE determination of some of the aldehydes assayed, such as malondialdehyde.…”
Section: Methods Validationmentioning
confidence: 73%
“…CE analysis involving use of these hydrazine-based derivatizing agents is relatively sensitive because linearity is established at g/ml level; however, by using a pre-concentration step, the determination of these aldehydes is feasible at g/l level, such as in air samples [15,18,20]. On the other hand, the majority of these electrophoretic methods have been applied to the determination of LMMAs in such simple matrices as air [10,12,15,18,20] or water [16,19] samples, and therefore very little work has been focused on their analysis in more complex matrices; to our knowledge, only human saliva [11] and food samples [14,17] have been assayed. For these reasons, it is clear that the determination of LMMAs through CE demands more sensitive approaches that do not cause detriment to the resolution and also that will extend their analysis to more complex analytical samples.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation